Sport science and coaching in paralympic swimming - Burkett, B. J.; Mellifont, R. B. (International Journal of Sports Science and Coaching, 2008)
This research documents the sport science and coaching interaction that occurred with a national swimming team from the 2002 World Championships, 2004 Athens Paralympic Games, and the 2006 World Championships. The research was driven by the head coach of the swimming program, and biomechanical measures were made during competition and in national training camps to provide feedback to coach and athlete. By understanding the swimmers' race strategy, a 10 percent improvement in performance was attained. This was followed by an additional 2.6 percent improvement resulting in a new world record time. In addition, race-pattern comparisons were made between swimmers with visually impairment or total blindness at the Sydney 2000 Games. Surprisingly, there was no difference in the race strategy between these swimmers, highlighting that the ability to "see" the opposition swimmer and racing them may not be as important as employing a suitable race strategy. A key point of difference in the race analysis conducted within this research, when compared to existing research, was the use of video feedback in conjunction with the calculated race parameters.